Metabolic changes in mulberry (Morus sp.) leaves due to leaf blight disease and its impact on silkworm rearing - Ghosh, Lipika; Ali, MR (University Journal of Zoology, Rajshahi University, 2007)
Key words: Metabolic changes; mulberry leaf; silkwork rearing; leaf blight; cocoon characters; Phyllostica sp. Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 111-116